2021
DOI: 10.1002/adem.202100214
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Fine Grain Size and Microhardness at the Interface of AZ31/Mg‐Y Composites

Abstract: AZ31/Mg‐Y/AZ31 composites are fabricated by hot rolling bonding. To identify the formation mechanism of the microstructure in the interface adjacent region, additional hot rolling or/and diffusion annealing are also conducted on the base of the initial AZ31/Mg‐Y/AZ31 composite. Scanning electron microscopy, energy dispersive spectroscopy, and electron backscatter diffraction are used to characterize the microstructures and chemical compositional distributions. Vicker's microhardness tests are conducted to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…Xian et al innovatively added an oxidant as an aggregation promoter and helped increase the conversion rate of the polymerization, resulting in a yield of up to 83.3%. [ 72 ] Besides, they found that the decrease of oxygen content and pyridine nitrogen content and the increase of pyrrole nitrogen content could make the FWHMs of CDs narrow, which was down to 20 nm. Another team produced CDs through microwave irradiation with the same precursor (D‐glucosamine hydrochloride and ethylenediamine) but different stoichiometry of the reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Xian et al innovatively added an oxidant as an aggregation promoter and helped increase the conversion rate of the polymerization, resulting in a yield of up to 83.3%. [ 72 ] Besides, they found that the decrease of oxygen content and pyridine nitrogen content and the increase of pyrrole nitrogen content could make the FWHMs of CDs narrow, which was down to 20 nm. Another team produced CDs through microwave irradiation with the same precursor (D‐glucosamine hydrochloride and ethylenediamine) but different stoichiometry of the reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Rotation is the dominant deformation mechanism of auxetic porous materials with chiral unit cell structures.Therefore, we analyze the internal rotational behavior of the chiral building block in the two-phase composite. Here, the initial configuration of chiral building block can be conceptually simplified to a generalized missing rib model, [36,37] comprising skeletal structures of rigid rods (referred to as ribs) with a defined length (a) connected through common joints, as illustrated in Figure 3a. We categorize the ribs into two groups based on their orientation relative to the loading direction.…”
Section: Mechanically Programmable Design Of Auxetic Composite Metama...mentioning
confidence: 99%
“…Among them, nonpolar (k< 3.5) polymers can be used in both n-type and p-type OTFTs, typical examples are CYTOP (2.1), PS (2.6), PαMS (2.6), PI (3.4), Parylene (3.0), and PMMA (3.5). Polar (k > 5) polymers are preferable for p-type OTFTs, [227] such as poly(vinyl alcohol) (PVA, 7.3) and relaxor ferroelectric polymer poly(vinylidene fluoridetrifluoroethylene-chlorofloroethylene)…”
Section: High-mobilitymentioning
confidence: 99%